Early Stage Clinical Trial of Ginger (Zingiber officinale) as an Add-on Antiepileptic Therapy in Children with Generalized Epilepsies (Khartoum Journal of Pharmaceutical Sciences, 2021)
Epilepsy is a disorder of the brain characterized by the generation of epileptic seizures. Botanicals and herbal materials including some parts from plants are prepared and taken in many ways for treatment of children ill with epilepsy. Conventional
Keywords: Ginger; Epilepsy; Add-on antiepileptic; Clinical trials